Carcass Traits, Physicochemical Characteristics, Fatty Acid, and Protein Profile of Khiew Phalee, Pradu Hang Dam and Broiler Chicken Meat - Phromnoi, S.; Chumngoen, W.; Puangmalee, T.; Nuchchanart, W. (Tropical Animal Science Journal, 2025)
This study investigated the carcass traits, physicochemical characteristics, fatty acid profile and protein profile of male Khiew-Phalee native (KP), Pradu Hang Dam (PHD), and commercial broiler chickens (CBR). All samples were collected from farms in Uttaradit province and determined the carcass traits and physicochemical characteristics, including proximate composition, pH, meat color, shear force, drip loss, cooking loss, and also analyzed the fatty acid profile, purine content, and protein profile. The results showed that carcass traits such as live weight, carcass weight, and cutting percentage showed a highly significant decrease (p